Поллианна: повесть / Элинор Портер - Портер Элинор Хантер (Чтение - лучшее учение, 2021)
Экземпляры: б/ф №10 (20211215) / Инвентарный номер: 40592 / Цена: / Сис.шифр: 84(7Сое) / Авт.знак: П 60 / ГРНТИ: 17.82.93 / ББК: 84(7Сое)